Análise da eficácia de três tipos de conteúdos de feedback no reconhecimento de emoções em expressões faciais: um estudo baseado em Torres e Gusso (2018) - Ribeiro, Guilherme de Melo Leão (2022)
Feedback is commonly used in organizations to make the emission of desirable behaviors more likely, but there is little experimental research on the effectiveness of different feedback contents. This study investigated the effects of three different feedback contents on the performance of 14 participants, undergraduate students in Business Administration, in an emotion recognition task in facial expressions through a computer application that enables arbitrary matching to sample. There was a handbook on emotions that could be consulted, and interviews were conducted at the end. The multiple baseline design between responses and between groups was used. Participants were divided into three experimental groups (four participants each) and a control group (two participants). Each experimental group received feedback content. The control group received no feedback. The following were analyzed: (a) the performance of each participant at baseline and after feedback, (b) the average performances of the experimental groups compared to the control group, and (c) the average performances between the experimental groups, according to the content feedback, (d) the number of times each participant consulted the handbook and whether the consultation had an effect on performance; and (e) verbal reports. The results indicated an increase in the average performance of all participants after the presentation of any feedback content and, through inferential statistics, an improvement in the performance of the experimental groups compared to the control group. The analysis of the effectiveness of each content indicated, however, similarities between the different types of feedback content. Further research is suggested to investigate the feedback contents in another type of task, with more participants and trials and greater methodological control